Mengapa Mahasiswa Cenderung Menghindari Politik? Memahami Apatisme dan Maknanya - Camberly, Graciella; Lydia Stevani; Jocelyn Samantha; Jelita Maharani; Stephanie Olga Colin; Agoes Dariyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to understand the meaning of political apathy among university students, identify the factors that contribute to this attitude, and explore strategies to foster civic awareness and active participation. This research employs a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with six students from Tarumanagara University representing various faculties and levels of organizational involvement. The findings reveal that apathy is understood as indifference, disengagement, or a deliberate choice to avoid political issues due to the perception that such issues are irrelevant to personal life or because of distrust toward the political system. The main factors contributing to apathy include limited resources, low psychological engagement, lack of social support, and low trust in government responsiveness. Although students generally possess adequate political understanding, fear of social and political risks discourages active participation. The conclusion of this study is that efforts to overcome apathy need to be carried out through strengthening civic education, providing safe spaces for discussion, social support from campuses, and utilizing digital media that is relevant for the younger generation. Keywords: Apathy, Civic Engagement, Phenomenology, Politics, University Students.